National-local dissonance and exacerbated vulnerabilities COVID-19 and PH governmental response - Lao, Maria Elissa J.; Berse, Pilar Preciousa P. (2023)
The chasm between good and bad governance widens during times of prolonged crisis. The COVID-19 pandemic proved how well governed countries could climb out of the initial waves of infection while others struggled or failed to provide substantial efforts to curb the disease.
Vulnerable groups, such as women, youth, children, the elderly, poor households, as well as communities that depend on the informal economy, with limited access to social and health services, are made even more vulnerable because of the uncertainties brought by the pandemic. Even non-traditional vulnerable groups, such as migrant workers and locally
stranded individuals have become vulnerable due to this unprecedented health crisis. This article attempts to examine how the disease has affected the lives of ordinary Filipinos, as they confronted not only an invisible enemy but also state-imposed COVID-19 measures that inadvertently left them in an even more precarious state. The authors argue that state-imposed COVID-19 measures increased the risk of already vulnerable groups rather than protect them. In doing so, the article attempts to identify the effects of the pandemic and corresponding government responses to (1) the plight of locally stranded individuals and
(2) community quarantines.
Keywords: COVID-19 pandemic -- Emergency managemet; COVID-19 pandemic -- Social conditions; Filipino foreign workers -- Social conditions -- COVID-19 pandemic